Positive Stereotypes Are Pervasive and Powerful. (July 2015) - Czopp, Alexander M.; Kay, Aaron C.; Cheryan, Sapna
Stereotypes and their associated category-based processes have traditionally been considered largely within the context of the negativity of their content and consequences, both among the general public and the scientific community. This review summarizes and integrates extant research on positive stereotypes, which are subjectively favorable beliefs about social groups, and examines their implications for individuals and groups directly targeted by such stereotypes. Furthermore, we examine the beneficial and adverse implications of positive stereotypes for interpersonal and intergroup relations, as well as the ways in which positive stereotypes, more so than negative stereotypes, may contribute to and perpetuate systemic differences in power and privilege.